1999
DOI: 10.1074/jbc.274.16.11170
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GMXCXXC Metal Binding Sites in the Copper-induced Redistribution of the Menkes Protein

Abstract: The Menkes protein (MNK or ATP7A) is a transmembrane, copper-transporting CPX-type ATPase, a subgroup of the extensive family of P-type ATPases. A striking feature of the protein is the presence of six metal binding sites (MBSs) in the N-terminal region with the highly conserved consensus sequence GMXCXXC. MNK is normally located in the trans-Golgi network (TGN) but has been shown to relocalize to the plasma membrane when cells are cultured in media containing high concentrations of copper. The experiments des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
130
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 32 publications
6
130
1
Order By: Relevance
“…The generation of stably transfected CHO-K1 cell lines (WT-ATP7B, MBD1-6del, MBD3-5del, wt-ATP7A, ATP7Am4 -6, and ATP7Am1-6) were described previously (42,43). In this study, "stably" and "transiently" expressed proteins refer to proteins expressed from integrated and nonintegrated plasmids, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of stably transfected CHO-K1 cell lines (WT-ATP7B, MBD1-6del, MBD3-5del, wt-ATP7A, ATP7Am4 -6, and ATP7Am1-6) were described previously (42,43). In this study, "stably" and "transiently" expressed proteins refer to proteins expressed from integrated and nonintegrated plasmids, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid Constructs-Plasmid cDNA constructs encoding wild type (WT) ATP7B, ATP7B (MBD1-6del), and ATP7B (MBD3-5del) were generated previously (42), as were plasmid constructs encoding WT-ATP7A, ATP7Am4 -6, and ATP7Am1-6 (43). Clusterin cDNA in pIREShyg1 (Clontech) was kindly provided by Saverio Bettuzzi (University of Parma, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Another potential function for the metalbinding domains is mediating copper-responsive cellular relocalization. For example, mutations in MNK domains 4 -6 interfere with the ability to traffic to the plasma membrane in response to elevated copper (30,31). Finally, some of the domains may interact specifically with the copper chaperone Atox1.…”
mentioning
confidence: 99%
“…Endogenous as well as overexpressed ATP7A and ATP7B were detected in the TGN in a wide variety of polarized and nonpolarized cell types under basal copper conditions, both in vitro and in vivo [9,11,12,14,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. In ATP7A, a putative TGN-targeting signal was identified within transmembrane helix 3 [54].…”
Section: Posttranslational Regulation Of Copper Transportmentioning
confidence: 99%
“…Barnes et al [68] demonstrated that copperinduced trafficking of endogenously expressed ATP7B in kidney-derived HEK293T cells, MDCK cells, Cos-7 cells, or primary kidney cells was perturbed, whereas copperdependent trafficking of ATP7A did take place in these same cell types. Reversible copper-dependent trafficking of ATP7A to the plasma membrane or post-Golgi vesicles in nonpolarized cells [11,[54][55][56][57][58] and specifically towards the basolateral membrane in polarized cells [59-62, 69, 70] was observed.…”
Section: Posttranslational Regulation Of Copper Transportmentioning
confidence: 99%